DENTAL SCREENING AND DMF-T SCORE ANALYSIS IN DESA RANDEGANSARI - Widjaja, Jennifer; Darmadi, Eveline Yulia; Fauziah, Yessy Andriani; Ameliana, Yemy; Amaliah, Nurfitri (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
Dental caries remains a prevalent public health issue, particularly in rural areas with limited access to dental care. This study aimed to assess the oral health status of residents in Randegansari Village through dental screening and DMF-T score analysis. A cross-sectional study was conducted on 15 participants aged 13–65 years. The results showed a high DMF-T score, with missing teeth contributing the most. The high prevalence of tooth loss and untreated caries indicated inadequate access to dental care and a lack of awareness regarding oral hygiene. The primary challenges identified were the absence of preventive measures and limited access to restorative treatment. To address this issue, educational programs on oral health, preventive interventions such as fluoride applications, and improved access to dental care are essential. The study concludes that increased community awareness and dental services are necessary to reduce caries prevalence and improve oral health in rural populations.